TRANSLATING OTHERNESS IN AMY TAN’S “THE JOY LUCK CLUB” - Deepa Vanjani (Езиков свят)
The Joy Luck Club by the Chinese American author Amy Tan is about the lives of four Chinese women born and raised in China and their American born daughters. The novel has been adapted into a 1993 film with the same name. The lives of the four families, with Chinese immigrant mothers and their Chinese American daughters intersect in the club named ‘Joy Luck Club’ in San Francisco. During this intersection there are issues pertaining to cultural identities, gender, immigrant lives, marginalisation and otherness. Language and its role in shaping identities comes to the fore as Chinese words often surface, as these words express the exact meaning for the mothers, but not so much for the daughters who are English speaking. How Tan puts the racial and cultural identities of the mothers and their daughters under a lens is interesting, for through the lens we see how Otherness manifests itself within the domain of families and outside of them. The present paper investigates ways by which the novel and film depict Otherness and how identities are formed by social interactions. Another area that will be investigated is that of fluidity of linguistic interactions as the author indulges in domestication and code switching.